Philippine Productivity Performance in the 1990s: An Assessment - Myrna S. Austria (Philippine Institute for Development Studies (PIDS), 2000)
This paper examines the total factor productivity performance (TFP) of the Philippines in the 1990s in order to provide a picture of the extent of the productivity concern that needs to be addressed in the Medium-Term National Action Agenda for Productivity, 2000-2004. The findings show that while the average TFP growth of the country has improved in the 1990s, it has nonetheless remained negative, a big contrast to the favorable productivity performance of the other ASEAN-Four. Positive productivity performance, however, has been registered during the trade liberalization period of 1986-1996. Among the different sectors, only mining, manufacturing and utilities registered positive TFP performance. Key issues and research gaps that need to be addressed were also identified.
Keywords: 330; productivity; trade liberalization; Produktivität; Handelsliberalisierung; Philippinen